1999
DOI: 10.1161/01.hyp.33.3.844
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Involvement of the Type 1 Angiotensin II Receptor Locus in Essential Hypertension

Abstract: Abstract-Components of the renin-angiotensin system play an important role in the normal regulation of blood pressure.We carried out a comprehensive genetic linkage study of the genes involved in the renin-angiotensin cascade in Finnish hypertensive twins and their affected siblings. We found no evidence for linkage between essential hypertension and the genes coding for renin, angiotensinogen, angiotensin-converting enzyme, or kallikrein 1 in the 329 hypertensive individuals of 142 families studied. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
3

Year Published

2000
2000
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(87 citation statements)
references
References 25 publications
4
80
0
3
Order By: Relevance
“…7,8,39 In Finnish sub-populations arising from the old region of early settlement, we have earlier observed that in alleles associated with complex diseases, such as essential hypertension and multiple sclerosis (MS), LD is detectable only over a greatly restricted interval. In such cases, LD was observed to span some 30-40 kb: examples are the angiotensin II receptor type-1 gene in hypertension and the HLA region of the golli-MBP gene in MS. [40][41][42] Our data should not discourage scientists from pursuing studies of samples from such genetic isolates. Because of the reductions in genetic, cultural, and environmental heterogeneity in these populations, phenotypic observations are better able to predict the underlying disease-predisposing genotypes, and since the affected individuals in these populations are most certainly related if one looks far enough back into the genealogy, their predisposing alleles may often be IBD.…”
Section: Discussionmentioning
confidence: 86%
“…7,8,39 In Finnish sub-populations arising from the old region of early settlement, we have earlier observed that in alleles associated with complex diseases, such as essential hypertension and multiple sclerosis (MS), LD is detectable only over a greatly restricted interval. In such cases, LD was observed to span some 30-40 kb: examples are the angiotensin II receptor type-1 gene in hypertension and the HLA region of the golli-MBP gene in MS. [40][41][42] Our data should not discourage scientists from pursuing studies of samples from such genetic isolates. Because of the reductions in genetic, cultural, and environmental heterogeneity in these populations, phenotypic observations are better able to predict the underlying disease-predisposing genotypes, and since the affected individuals in these populations are most certainly related if one looks far enough back into the genealogy, their predisposing alleles may often be IBD.…”
Section: Discussionmentioning
confidence: 86%
“…[1][2][3][4][5][6] It is thus of particular appeal in investigations aimed at identifying QTLs implicated in EHT and allied clinical manifestations. So far, however, both positive associations with EHT, family history of EHT and intermediate phenotypes [10][11][12][18][19][20][21][22][23] and negative results as for association or linkage studies with EHT [24][25][26][27][28][29][30][31][32][33][34][35][36] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown an association between the AT1R 1166C allele and hypertension, especially severe hypertension (Bonnardeaux et al 1994;Hingorani et al 1995;Wang et al 1997;Kainulainen et al 1999;Henskens et al 2003) and in pregnant women (Nalogowska-Glosnicka et al 2000; Kobashi et al 2004). Other groups refuted these results (Schmidt et al 1997;Zhang et al 2000;Staessen et al 2001;Iliadou et al 2002;Ono et al 2003).…”
Section: Genetic Variants In the Angiotensin II Receptor Type Imentioning
confidence: 97%